Aplicación de la búsqueda tabú en la resolución del problema capacitado de lotificación en sistemas de producción multinivel: un estado del arte (2020)
In this work, a study of the application of the taboo search for the resolution of the problem of production planning in multilevel systems with capacity restrictions is approached from the literature. This family of problems is classified in the literature as Np-Hard. Relaxation and search strategies, especially Taboo Search, have played a decisive role in the development of alternative solutions for this type of problem, allowing to obtain solutions close to the optimal minimum cost value, in operationally acceptable times. The purpose of this article is to collect, describe and analyze the use and application of taboo search in the solution of the problem of lotification in multilevel production systems. Contemplating the large number of variations of the problem and emphasizing the methodology used and the configuration of the search, it is intended to establish the baseline for the development of new solution algorithms for the lotification problem.